The Evaluation of Green Behaviour Implementation in AL Fazza Nature School to Become Adiwiyata School - Sunarya, Asri Ismayati; Nurhayati, Mafizatun (ARE Publisher, 2024)
The aim of this study is the evaluation of green behaviour implementation in Al Fazza Nature School to become an Adiwiyata school. The focus of the study is to comprehend how effective the environmental values applied in school events are and to analyse the strategy conducted by Al Fazza Nature School to become an Adiwiyata school. This study used a qualitative approach by conducting a case study method in Al Fazza Nature School. The data were taken from in-depth interviews, participant observation, and school notes analysis. The study result showed that the implementation of green behaviour in Al Fazza Nature School has been in line with environmental education principles according to the ministerial regulation of the Environmental Ministry (Permen LHK) number 23, year 2022, such as waste management using the 3R method (reduce, reuse, recycle) and the integration of environmental values in the school curriculum. However, there were several challenges to becoming an Adiwiyata school, including the lack of facilities or places related to energy conservation, teachers and students lack of commitment, and the need to create innovation related to environmental conservation. In order to make a strategic step, the school is expected to build a special team to carry out the process towards Adiwiyata.